Psikhologicheskie i metodicheskie osobennosti obucheniya sportsmenov meditatsii - Shlakhter, V. V. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The role of meditation is described and some advice is given for combat sports how to effective use musical-rhythmic meditation for the preparation of the athletes.